EATING DISORDERS PADA SISWA SMA DI KOTA GORONTALO - Tumenggung, Imran; TAlibo, Sofyawati D. (JOURNAL HEALTH AND NUTRITIONS, 2018)
ABSTRACT Special report and research on eating disorders (EDs) and its determinant are not very much exist. There are three eating disorders categories namely anorexia nervosa (AN), bulimia nervosa (BN) and binge eating disorder (BED) that give further impact namely several health disorders problem. Objective it aims to investigate prevalence of EDs and its determinant at students of SMA in Gorontalo City. Research design it is quantitative research with analytical survey method and it applies cross sectional study. Research samples are 350 students of SMA in Gorontalo City. Research hypothesis is Ha: there is influence of knowledge on nutrition, mass media, body image and self confidence on EDs. Ho: there is no influence of knowledge on nutrition, mass media, body image and self confidence on Eds. Finding univariate analysis shows that mostly students of SMA in Gorontalo City have high nutrition knowledge (59,14%), it is not influenced by mass media (73,14%), body image is good (67,42%) and level of self confidence is high (70,57%). Prevalence of EDs is 9,1%. Bivariate analysis shows that knowledge on nutrition has p value for 0,32, p value of mass media for 0,00, p value of body image for 0,00 and p value of body image for 0,00. Conclusion knowledge on nutrition does not correlate with eating disorders at students of SMA in Gorontalo City. Then, mass media, body image and self confidence are correlated with eating disorders incident at students of SMA in Gorontalo City. Keywords: Eating Disorders, Students of SMA ABSTRAK Laporan kasus dan penelitian mengenai kejadian eating disorders (EDs) dan determinannya belum banyak dilakukan. Tiga kategori eating disorders yaitu anoreksia nervosa (AN), bulimia nervosa (BN), dan binge eating disorder (BED) memberikan dampak yang lebih lanjut yaitu berbagai masalah gangguan kesehatan. Penelitian ini bertujuan untuk mengetahui prevalensi EDs dan determinannya pada siswa SMA di kota Gorontalo. Jenis penelitian kuantitatif dengan metode survei analitik, menggunakan rancangan studi potong lintang. Sampel penelitian adalah siswa SMA di kota Gorontalo sebanyak 350 orang. Analisis data dilakukan dengan cara analisis univariat dan analisis bivariat. Analisis univariat menunjukkan bahwa sebagian besar siswa SMA di kota Gorontalo memiliki pengetahuan gizi yang tinggi (59,14%), tidak dipengaruhi media massa (73,14%), citra tubuh yang baik (67,42%), dan tingkat percaya diri yang tinggi (70,57%). Prevalensi EDs sebanyak 9,1%. Analisis bivariat menunjukkan bahwa pengetahuan gizi tidak berhubungan dengan kejadian eating disorders pada siswa SMA di kota Gorontalo. Pengaruh media massa, citra tubuh, dan percaya diri berhubungan dengan kejadian eating disorders pada siswa SMA di kota Gorontalo. Kata Kunci: Eating Disorders, Siswa SMA